If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + 8 = -12x Reorder the terms: 8 + -3y = -12x Solving 8 + -3y = -12x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3y = -8 + -12x Combine like terms: 8 + -8 = 0 0 + -3y = -8 + -12x -3y = -8 + -12x Divide each side by '-3'. y = 2.666666667 + 4x Simplifying y = 2.666666667 + 4x
| 4(x-2)/6=2(x+8)/13 | | 2x^2+2x=-74 | | (3/4)(4-x)=3-x | | 4(x-3)+2x=3(2x-5) | | 36x-63=36x+18 | | 3s(2)-5s+9=0 | | 3c(x+2)-5=c(x-3) | | 2=-5n+4n | | 5.5=-2+d | | 4(3q-2)=16 | | x^2-7x+1.25=0 | | 5.4t+14.6-10.1t=12.8-3.5t | | -2--14= | | 4(x+1)/6=3x-4 | | -2+-14= | | 50,000=28 | | 5(3+5x)-5=160 | | 2a-9=2a-9 | | 0.50x+0.35(70)=47.5 | | 6=.0002x^2-.316x+127.9 | | 24=7x-4(2x-4) | | 3x=4y | | 4x-6=9x+1 | | 2(4x-3)-8=-3(4x-5) | | -p-6p=0 | | 0.58333333333x-0.25=5 | | 6u+14= | | 118=2x-3(4x+12) | | 5(3x-4)-3x-2=14 | | 90=12X-16 | | 6u+14=-12-2u | | 12=-4*-6x-3 |